Early echocardiographic predictors of increased left ventricular end-diastolic pressure three months after myocardial infarction in rats - Azevedo, Paula S. [UNESP]; Polegato, Bertha F. [UNESP]; Minicucci, Marcos F. [UNESP]; Pio, Stephan M. [UNESP]; Silva, Igor A. [UNESP]; Santos, Priscila P. [UNESP]; Okoshi, Katashi [UNESP]; Paiva, Sergio A. R. [UNESP]; Zornoff, Leonardo A. M. [UNESP] (International Scientific Information, 2012)
Background: The objective of this study was to determine the early echocardiographic predictors of elevated left ventricular end-diastolic pressure (LVEDP) after a long follow-up period in the infarcted rat model. Material/Methods: Five days and three months after surgery, sham and infarcted animals were subjected to transthoracic echocardiography. Regression analysis and receiver-operating characteristic (ROC) curve were performed for predicting increased LVEDP 3 months after MI. Results: Among all of the variables, assessed 5 days after myocardial infarction, infarct size (OR: 0.760; CI 95% 0.563-0.900; p=0.005), end-systolic area (ESA) (OR: 0.761; CI 95% 0.564-0.900; p=0.008), fractional area change (FAC) (OR: 0.771; CI 95% 0.574-0.907; p=0.003), and posterior wall-shortening velocity (PWSV) (OR: 0.703; CI 95% 0.502-0.860; p=0.048) were predictors of increased LVEDP. The LVEDP was 3.6±1.8 mmHg in the control group and 9.4±7.8 mmHg among the infarcted animals (p=0.007). Considering the critical value of predictor variables in inducing cardiac dysfunction, the cut-off value was 35% for infarct size, 0.33 cm2 for ESA, 40% for FAC, and 26 mm/s for PWSV. Conclusions: Infarct size, FAC, ESA, and PWSV, assessed five days after myocardial infarction, can be used to estimate an increased LVEDP three months following the coronary occlusion. © Med Sci Monit.
Keywords: Cardiac function; Heart failure; Remodelingbr